Authenticity or Bust - Duncan, Chris (Archivaria, 2010)
The notion of authenticity has become a regular preoccupation within archival literature, and concern has been aired in numerous articles about its intention, achievability, or even relevance in a records management context. This article investigates these concerns by reconstructing the meaning of the word in relation to its original function through an evaluation of the impact of “memory,” “proof,” and “belief” on its veracity. Such investigations ultimately point to social construction as the most purposeful manifestation of authenticity, where the authentes record provides the truest of templates for this most polemic of attributes. RÉSUMÉ La notion de l’authenticité est devenue une préoccupation constante dans la littérature archivistique et de nombreux articles ont été consacrés à son intention, sa réalisation, voire même sa pertinence dans un contexte de gestion de documents. L’article explore ces questions en examinant le sens même du mot « authenticité » en lien avec sa fonction d’origine, à partir d’une évaluation des façons dont « la mémoire », « la preuve » et « les croyances » agissent sur sa véracité. De telles analyses concluent que la construction sociale est la manifestation la plus palpable de l’authenticité, où les documents authentes offrent le meilleur gabarit pour cette caractéristique polémique.